Electric Grid Modernization - Ghofrani, Mahmoud (IntechOpen, 2022)
Electrical grids worldwide are experiencing major changes in terms of energy generation, transmission, delivery, and distribution in order to enhance the entire system's control, reliability, efficiency, and safety. Advanced energy systems and technologies such as renewable sources of energy, energy storage systems, and electric vehicles (EVs) as well as equipment such as sensors, smart meters, and communication devices along with innovations in computing technologies, machine learning, and data analytics are used to modernize the electric grid and the way it is planned, operated, and managed. This book provides an overview of several aspects of grid modernization including micro-grids, smart grids, energy storage, and communication systems.